Searching for an alternative to economic partnership agreements - Bouët, Antoine; Laborde Debucquet, David; Mevel, Simon (International Food Policy Research Institute, 2007)
On January 1, 2008, Economic Partnerships Agreements (EPAs), currently being negotiated between the European Union (EU) and nearly 80 African, Caribbean, and Pacific (ACP) countries, are expected to replace the Cotonou Agreement, which has governed trade relations between these countries since 2000. The Cotonou Agreement, implemented through a waiver from the World Trade Organization (WTO), expires on December 31, 2007. At the second EU-Africa summit, held in Lisbon on December 8–9, trade issues have been a major bone of contention, with several African heads of state denouncing the way the negotiation had been led by the European Commission. At the end of the summit, the Commission agreed to continue EPA negotiations in 2008.